ANALISIS LAPORAN REALISASI ANGGARAN UNTUK MENGUKUR KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN BONE - Ruliaty Ruliaty; Ismail Badollahi; A Indah Nurfadillah (INVOICE : JURNAL ILMU AKUNTANSI, 2019)
The results of the study show that: First, the independence of the Bone District Government in meeting the funding needs for the implementation of government tasks, development, and social services to the community is still very low and even experiences ups and downs from year to year, namely from 4.19% in in 2014 became 4.33% in 2015 and 3.01% in 2016. Where there was an increase in regional independence which subsequently decreased in 2015. Secondly, the Performance of the Regional Government of Bone Regency in realizing the original regional income was classified as ineffective and classified as efficient , namely in 2014 had an effectiveness ratio of 62.19% and an efficiency ratio of 2.13% then in 2015 had an effectiveness ratio of 59.53% and an efficient ratio of 2.71%, and in 2016 had an effectiveness ratio of 32.96% efficient ratio of 2.16%. Third, Most of which are owned by the Regional Government of Bone Regency are still prioritized to meet the needs of the bell operation rather than capital expenditure.